Effects of postnatal formaldehyde exposure on pyramidal cell number, volume of cell layer in hippocampus and hemisphere in the rat: A stereological study - Sarsilmaz, Mustafa; Kaplan, Suleyman; Songur, Ahmet; Colakoglu, Serdar; Aslan, Huseyin; Tunc, Ayten Turkkani; Bas, Orhan (Elsevier Science Bv, 2007)
The purpose of the present study was to determine whether exposure of neonatal rats to formaldehyde (FA) had either early or delayed effects on the numbers of pyramidal cells in the cornu ammonis (CA) of the hippocampus. Neonatal Wistar rats were exposed to 0 ppm (control group), 6 ppm and 12 ppm (high concentration group) of FA concentrations throughout the 30-day period following the birth by placing them for 6 h/day in a glass chamber containing FA vapor. Then, some of the animals from each FA-treated group were anesthetized and decapitated at the day 30, and the remaining ones were killed at the day 90. The brains were removed immediately and fixed in 10% neutral-buffered FA solution. The Cavalieri principle was used to determine the volumes of the CA and the entire cerebral hemisphere. The optical fractionator counting method was used to estimate the total number of pyramidal cells in the CA. The appearance of pyramidal cells was normal under light microscopy at both postnatal day (PND) 30 and PND 90 in all groups. There were concentration-related volume changes of CA at PND 30 and PND 90; low concentration of FA significantly increased, whereas high concentration decreased the volume of CA in comparison of the control at PND 30. Importantly, high concentration of FA at PND 90 increased the volume of CA in comparison of the low concentration but not with the control. Furthermore, low and high concentrations of FA decreased the volume of hemisphere at PND 30, whereas a reverse effect of these concentrations was observed at the hemisphere of PND 90 in comparison of the control. In both CA and cerebral hemisphere, an age-related volume decrease in both control and low/high concentration groups were found. On the other hand, there were significant age-related reductions in the total number of pyramidal cells at 90 days of age irrespective of the groups examined. Rats treated with high concentration FA were seen to have significantly fewer pyramidal cell neurons than either the animals treated with low concentration FA or control groups (p < 0.01). These observations indicate that pyramidal cells in the hippocampus may be vulnerable to FA exposure during the early period of life. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: formaldehyde; hippocampus; pyramidal cell; hemisphere; stereology; volume; Cavalieri principle